2022
DOI: 10.1111/1365-2745.13910
|View full text |Cite
|
Sign up to set email alerts
|

Dancing with Douglas‐fir: Determinism dominates fungal community assembly processes

Abstract: Fungal communities can influence the productivity, composition and survival of trees through cycling nutrients, providing resources and altering pathogens. Thus, shifts in fungal communities could impact forests by altering interactions between trees and their environments. Fungal community composition may be shaped by stochastic and deterministic processes such as dispersal limitation, environmental filtering and partner specificity between trees and fungi. For tree species with large geographical ranges, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 88 publications
0
4
1
Order By: Relevance
“…Our observation in the context of different habitats is in line with the results of recent large-scale studies in natural soil from different habitats across Scotland ( Powell et al, 2015 ), suburban agricultural districts of Shanghai, China ( Li et al, 2021 ), and a wine-growing region of Italy ( Larsen et al, 2022 ). In contrast to our finding, however, Birch et al (2022) , who reported that deterministic processes, particularly homogenizing selection, dominated fungal communities along an 1,800 km transect of North America across Pseudotsuga forests. Our results indicate a greater tendency toward stochastic processes, which is inconsistent with the seminal work of Zheng et al (2021) , who highlighted a substantial divergence among whole fungal communities and the AM and EM fungal community subsets within and among 12 forest ecosystems along a large latitudinal gradient.…”
Section: Discussioncontrasting
confidence: 99%
“…Our observation in the context of different habitats is in line with the results of recent large-scale studies in natural soil from different habitats across Scotland ( Powell et al, 2015 ), suburban agricultural districts of Shanghai, China ( Li et al, 2021 ), and a wine-growing region of Italy ( Larsen et al, 2022 ). In contrast to our finding, however, Birch et al (2022) , who reported that deterministic processes, particularly homogenizing selection, dominated fungal communities along an 1,800 km transect of North America across Pseudotsuga forests. Our results indicate a greater tendency toward stochastic processes, which is inconsistent with the seminal work of Zheng et al (2021) , who highlighted a substantial divergence among whole fungal communities and the AM and EM fungal community subsets within and among 12 forest ecosystems along a large latitudinal gradient.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, previous studies demonstrated that soil fungal community assemblies were strongly shaped by deterministic (niche-based) factors (e.g., [ 40 , 41 ]). For root-associated fungal communities, deterministic processes dominated at most of the sites ( 42 ), while neutral processes still had a minor influence on community assembly and might be important in spatially isolated communities as well as those with strong gradients of fungal diversity ( 42 , 43 ). According to the lower migration rate of the leaf compartment than that of the root and soil compartments, our results suggested that fungal communities in the phyllosphere were less affected by deterministic process than were those in the other two compartments.…”
Section: Discussionmentioning
confidence: 99%
“…These clues indicate that variation in the composition and structure of the root endophytic microbiota is non-random. Interestingly, recent studies applying the ecological null modeling framework have confirmed that the assembly of the root endophytic microbiota is primarily affected by stochastic processes ( Table 1 ; Figure 2 ) ( Birch et al., 2022 ; Tian et al., 2022 ; Zhong et al., 2022 ). Although this finding explains why stochastic assembly dominates the endophytic root microbiota: via priority effects—microorganisms that arrive first at a location have positive or negative effects on those that arrive later—and competitive exclusion, it contradicts the previously established consensus that roots are a highly selective environment that recruits specific microbial taxa via different exudation patterns.…”
Section: Assembly Processes Inconsistency Of Root Endophytic Microbio...mentioning
confidence: 87%
“…Detailed information on each treatment group can be found in the original literature cited. Brassica napus ( Bell et al., 2022 ), grass species ( Zhong et al., 2022 ), Panicum miliaceum ( Tian et al., 2022 ); Pseudotsuga menziesii (PM) ( Birch et al., 2022 ), Populus ( Dove et al., 2021 ), and Camellia sinensis (CS; unpublished data).…”
Section: Assembly Processes Inconsistency Of Root Endophytic Microbio...mentioning
confidence: 99%